Analisis Faktor-Faktor Yang Mempengaruhi Persistensi Laba - Rika Nur Ismawati; Afifa Nurhanifah (AKUNTANSI 45, 2024)
Companies that can achieve profits on target can be categorized as good companies. The quality of the company's profit can be demonstrated by persistent profits. Indicators affecting the persistence of profit will be shown objectively in the study. Sales volatility, cash flow volatility, operating cash flow, and company size are some of them. Manufacturing companies in the industrial and consumption sectors of the food and beverage subsector that are actively listed on the Indonesia Stock Exchange from 2018 to 2022 are the focus of this study. Using purposive sampling criteria, 145 observational data will be assessed in this study. The technique or method of analysis used is multiple linear regression analysis. This study showed that among the four independent variables tested against profit persistence, there were three independent variables that were influential. Among them are sales volatility, cash flow volatility, and operating cash flow. So that the company to measure and get persistent profits must pay attention to the level of sales, and the use of operating cash flow. With persistent profits can show the quality of the company's profits that will provide a good long-term assessment for investors.